Cognitive behavioral therapy’s impact on anxiety, depression, and quality of life in patients with head and neck cancer: a systematic review - Wang, Xi; Li, Wenjuan; Zhao, Tingting; Jin, Qi; Wang, Huan (Frontiers in Psychology, 2025)
ObjectivePatients with head and neck cancer frequently encounter challenges related to emotional fluctuations and psychological distress. Current research uniformly suggests that cognitive behavioral therapy has considerable potential in clinical settings for alleviating emotional issues and improving the quality of life in cancer patients. However, the therapeutic efficacy of CBT specifically for patients with head and neck cancer remains uncertain. This paper aims to systematically evaluate the intervention effects of cognitive behavioral therapy on anxiety, depression, and quality of life among patients with head and neck cancer.MethodA comprehensive search was conducted across 11 databases, covering the period from the inception of the databases to May 2024. Four reviewers were responsible for study selection, data extraction, and quality assessment. This systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines.ResultsSix randomized controlled trials were included, encompassing a total of 657 patients with head and neck cancer. The systematic review revealed that anxiety scores (SMD = −0.61, 95% CI: −1.02 to −0.20, p = 0.003) and depression scores (SMD = −0.83, 95% CI: −1.38 to −0.29, p = 0.003) were significantly lower in the CBT group compared to the control group; however, the effect of CBT on improving the quality of life (SMD = 0.56, 95% CI: −0.15 to 1.26, p = 0. 122) was not statistically significant.ConclusionCognitive Behavioral Therapy is an effective approach for alleviating anxiety and depression in patients with head and neck cancer; however, its impact on improving their quality of life is not significant. The observed heterogeneity across studies may be attributed to several factors such as intervention program design, sample size, outcome assessment tools, and external social influences. Future research should employ more rigorous methodological designs and incorporate larger-sample, multicenter randomized controlled trials to further validate the effectiveness of CBT.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024583519, identifier CRD42024583519.